2022
DOI: 10.4103/ijo.ijo_2006_21
|View full text |Cite
|
Sign up to set email alerts
|

Funduscopy-guided fluorescein angiography-free focal laser photocoagulation for central serous chorioretinopathy

Abstract: Purpose: To identify and correlate hypopigmented spots on fundoscopy with the leakage points on fluorescein angiography (FA) in patients with central serous chorioretinopathy (CSCR) to provide criteria for FA-free focal laser photocoagulation (FLP). Methods: Fifty consecutive patients of acute CSCR were evaluated between March and October 2019 confirming the inclusion and exclusion criteria. Colocalization of leakage points with discrete hypopigmented spots on clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A total of 83% of participants overall knew something about mucormycosis, and 86% understood that this was an emergency. Among the participants, more than 50% were unaware that diabetes raises the risk of mucormycosis [ 12 ]. One study from Bangladesh found that the majority of pupils (63.8%) spent close to two hours researching COVID-19 and Black Fungus (Mucormycosis) on electronic and social media.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 83% of participants overall knew something about mucormycosis, and 86% understood that this was an emergency. Among the participants, more than 50% were unaware that diabetes raises the risk of mucormycosis [ 12 ]. One study from Bangladesh found that the majority of pupils (63.8%) spent close to two hours researching COVID-19 and Black Fungus (Mucormycosis) on electronic and social media.…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescein angiography (FAG) allows to observe leakage of fluid into the subretinal space through the defects in RPE [58]. In CSC, usually, two types of patterns can be seen.…”
Section: Multimodal Imagesmentioning
confidence: 99%